Long-term survival outcomes of pediatric adrenal malignancies: An analysis with the upstaged SEER registry during 2000-2019 - Lv, Zemin; Yu, Yunyun; Luo, Yangmei; Lin, Song; Xiang, Xuang; Mao, Xiaowen; Cheng, Shigang (Frontiers in Endocrinology, 2022)
Objective: To investigate the clinicopathological characteristics and long-term survival outcomes of pediatric adrenal malignancies. Method: This study retrospectively analyzed children with pathologically confirmed pediatric adrenal malignancies from Surveillance, Epidemiology, and End Results Database from 2000 to 2019. Kaplan-Meier curve was used to assess the overall survival (OS) and cancer-special survival (CSS), and the Log-Rank method was used to calculate statistical differences. Cox proportional hazards model and Fine-and-Grey model were used to calculate the hazard ratio (HR) of all-cause mortality risk and the sub-distribution HR (sHR) of disease-specific mortality risk, respectively, and their corresponding 95% confidence intervals (CI). Results: 1601 children were included in the study in which 1335 (83.4%) neuroblastoma, 151 (9.4%) ganglioneuroblastoma, 89 (5.6%) adrenocortical carcinoma, and 26 (1.6%) were diagnosed with other types malignancies. Metastatic disease accounted for the largest proportion (69.3%), and the proportion of metastases diagnosed by neuroblastoma was higher than that of adrenocortical carcinoma and ganglioneuroblastoma (73.9% vs. 45.7% vs. 47.2%). The 5-year OS and CSS of all cohort were 69.5% and 70.5%, respectively. Adrenal cortical carcinoma had the worst prognosis, with 5-year OS and CSS of 52.5% and 53.1%, respectively. Patients in recent years had no better OS and CSS than in previous years at diagnosis. The tumor stage remained the main prognostic predictor. Compared to metastatic adrenal tumors, the risk of all-cause mortality (adjusted HR: 0.12, 95% CI: 0.06-0.25, P < 0.001) and the risk of disease-specific mortality (adjusted sHR: 0.11, 95% CI: 0.05-0.25, P<0.001) was significantly lower for patients with localized diseases. Additionally, higher age, adrenal cortical carcinoma, and lack of complete tumor resection are independent risk factors for poor prognosis. Furthermore, it was found that the prognosis of patients who received chemotherapy was worse than those who did not, mainly because the former mostly had metastasis at the presentation and complete resection of the tumor cannot be achieved. Conclusion: The clinicopathological characteristics of pediatric adrenal malignancies have not changed significantly in the past two decades, while the prognosis of patients has improved. Early diagnosis of disease and complete resection of local tumors are the keys to improving prognosis.